PENGARUH GOOD CORPORATE GOVERNANCE DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia tahun 20112015) - Ngedo, Ariance Inya; ., Sugiarti; Astuti, Titiek Puji (Jurnal Bisnis dan Kewirausahaan, 2019)
This study aims to examine the Influence of Good Corporate Governance and Corporate Social Responsibility to Financial Performance. The dependent variable used in this study is the financial performance which is measured by return on equity. The independent variables in this study are good corporate governance which is proxy with size of board of commissioner, percentage of independent commissioner, size of audit committee, audit quality and corporate social responsibility. This study uses return on assets (ROA), leverage and firm size as control variables. The population in this study are manufacturing companies listed in the Indonesia Stock Exchange in period 2011-2015. The samples in this study are 50 companies selected by using purposive sampling method. This study uses panel data regression analysis as an analytical tool. The results showed that: 1) The size of the board of commissioners has no positive effect to financial performance. 2) The percentage of independent commissioners has a positive effect to financial performance. 3) The size of the audit committee has no positive effect to financial performance. 4) Audit quality does not have a positive effect to financial performance. 5) Corporate social responsibility has no positive effect to financial performance. 6) Return on assets has a positive effect to financial performance. 7) Leverage has a positive effect to financial performance. 8) The firm size has no positive effect to financial performance.